IFRSs Adoption and its Influence on Financial Perfor-mance of Listed Consumer Goods Companies in Nigeria - Shittu Aliu Balogun; Sanyaolu Wasiu Abiodun; Job-Olatunji Kehinde Asamu (Journal of Accounting Research, Organization and Economics, 2019)
AbstractObjective – This study examined the effect of IFRS adoption on financial performance of Listed Consumer Goods Companies in Nigeria. Design/methodology – The study selected 10 out of all the 28 Listed Consumer Goods Companies in Nigeria. Ex post facto research design was adopted and regression analysis through the aid of Eviews 9 was employed in analyzing the effect of IFRS adoption on performance of the selected listed companies. Results – The findings revealed that IFRS adoption has significant positive effect on return on total asset, IFRS adoption has negative insignificant effect on interest coverage ratio, significant positive effect on basic earnings power ratio and that IFRS adoption has negative insignificant effect on leverage. Based on the findings, the study concluded that IFRS adoption has joint significant effect on Return on asset, on Basic earnings power and on Interest coverage while the reverse was the case for financial leverage. Research limitations/implications – This study is limited in the context of consumer goods companies only. Future studies can extend the result of this study by investigating other industry in identifying the implication of IFRS adoption in their businesses.